Peer contagion dynamics in the friendships of children with ADHD. (1st March 2022) - Normand, Sébastien; Lambert, Maude; Guiet, Joanna; Brendgen, Mara; Bakeman, Roger; Mikami, Amori Yee
Abstract : Background: Friendships in middle childhood carry high developmental significance. The majority of children with attention‐deficit/hyperactivity disorder (ADHD) have few friendships, unstable friendships, or poor relationship quality in any friendships they have. The current study used time‐window sequential analysis to map the dynamics within the friendships of children with ADHD, specifically the peer contagion processes of dyadic mutuality and coercive joining. Methods: Participants were 164 dyads consisting of a target child with ADHD and peer problems (age 6–11 years; 68% male; and 73% white) and a reciprocated friend. Dyads were observed in the lab during a cooperative task eliciting verbal negotiation processes to decide how to share a limited resource and during a fast‐paced, engrossing, and competitive task. Both tasks were designed to mirror the real‐world interactions of friends. Sequences of dyadic mutuality (i.e., reciprocity of positive affect and positive behaviors) and coercive joining (i.e., reciprocity of aggressive, controlling, and rule‐breaking behaviors) between target children and friends were coded. Results: Regarding dyadic mutuality, target children reciprocated their friends' positive affect in both tasks. They also reciprocated their friends' positive behaviors but only in the cooperative task. In contrast, they only reciprocated their friends' coercive joining behaviors in the competitive task. Medium to large reciprocity effects was found for 36%–53% (dyadic mutuality) and 38%–55% (coercive joining) of target children. Conclusions: These results extend findings of peer contagion processes to the friendships of children with ADHD and suggest that contagion may vary according to interaction context (i.e., competition vs. cooperation). Understanding the spread of peer contagion may illuminate how children with ADHD and their friends influence each other's adjustment over time and may guide friendship‐focused psychosocial interventions for this population.